Student Discipline and Learning Facilities as Predictors of Teacher Motivation: A Study of Public Elementary Schools in Rural Indonesia - Fitriyanti Fitriyanti; Bukman Lian; Mahasir Mahasir (Journal of Social Work and Science Education, 2027)
Teacher motivation is fundamental to instructional quality, yet research examining its contextual determinants in rural elementary schools remains limited. This study investigated the effects of student discipline and learning facilities on teacher motivation in public elementary schools in Semendawai Barat District, Indonesia. A quantitative cross-sectional survey design was employed with a sample of 60 teachers selected purposively from three representative schools. Data were collected using validated Likert-scale questionnaires measuring student discipline, learning facilities, and teacher motivation. Multiple linear regression analysis revealed that student discipline significantly predicted teacher motivation (β = 0.506, p < 0.001), and learning facilities also demonstrated a significant positive effect (β = 0.335, p < 0.001). Together, both predictors explained 77.3% of the variance in teacher motivation (R² = 0.773, adjusted R² = 0.769). Student discipline emerged as the stronger predictor, suggesting that classroom behavioral climate is particularly influential in shaping teachers’ professional motivation. The findings indicate that teacher motivation is substantially shaped by the immediate teaching environment rather than being solely an individual psychological attribute. Strengthening student discipline through consistent school policies and improving learning facilities through targeted resource allocation should be integrated priorities in elementary school management. This study contributes empirical evidence from a rural Indonesian context to the growing literature on teacher motivation as an ecological construct.